Bisimulations, Games, and Logic - Nielsen, Mogens; Clausen, Christian (BRICS Report Series, 1994)
In a recent paper by Joyal, Nielsen, and Winskel, bisimulation is defined in an abstract and uniform way across a wide range of different models for concurrency. In this paper, following a recent trend in theoretical computer science, we characterize their abstract definition game-theoretically and logically in a non-interleaving model. Our characterizations appear as surprisingly simple extensions of corresponding characterizations of interleaving bisimulation.